Šamanizm kak sociokulʹturnyj obʺekt gosudarstvennogo regulirovanija obyčno-pravovoj sfery Vostočnoj Sibiri XIX v. - Arzumanov, Igor A. (Czasopismo Prawno-Historyczne, 2018)
The main purpose of this research is to analyze the organization of the norms of the common law codification in the 19th century in Eastern Siberia. The above mentioned organization was taking place in the stream of ethno-consolidation processes. The regulation of social relationships in the autochthonous socio-cultural environment took place in the framework of the mythoreligious shamanism complex. Moreover, it appeared as the main form of the ideological system. The aforementioned fact influenced the specific character of the process of the political and legal integration of the indigenous organization of the state’s fiscal activity on the executive managerial level. The unification of the managerial system with the codification of the common law of the indigenous populations was carried out in two stages. The first stage was comprised of the stratification of the indigenous (yasachny) community into three layers. Furthermore, each layer reflected the specific character and tribal structure of each self-government as well as the way of life of the indigenous denizens of Eastern Siberia. The second stage consisted of the legalization of the management system of the common law of the indigenous inhabitants as well as of the predetermination of the parameters of the legislative activity of the administration in light of the common tasks connected with the realization of the integration function of the state.